2022
DOI: 10.3390/plants11070880
|View full text |Cite
|
Sign up to set email alerts
|

Ethnomedicinal Plants in Herbal Remedies Used for Treatment of Skin Diseases by Traditional Healers in Songkhla Province, Thailand

Abstract: Skin disorders are a worldwide health problem that normally affect human life. A traditional healer is an important expert in researching notable medicinal plants for skin disease treatment. This study aimed to determine the traditional knowledge and the use of medicinal plants for the treatment of skin diseases among traditional healers in the Songkhla province, Thailand. The ethnobotanical information was collected from experienced traditional healers by semi-structured interviews and participant observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
6
0
1

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 90 publications
2
6
0
1
Order By: Relevance
“…The analysis of plant life forms for the reported TMPs revealed that trees constituted a significant proportion (50%), followed by herbs (27%) and shrubs (23) (Figure 3). This study finding is consistent with habitats of TMPs from other studies on a similar topic (Saising et al 2022). The dominant use of trees could be influenced by the region's tropical climate that upholds the growth of a wide variety of trees (Sikuku et al 2023) and the ethnobotanical familiarity of the life form .…”
Section: Life Forms and Sources Of Medicinal Plantssupporting
confidence: 90%
See 3 more Smart Citations
“…The analysis of plant life forms for the reported TMPs revealed that trees constituted a significant proportion (50%), followed by herbs (27%) and shrubs (23) (Figure 3). This study finding is consistent with habitats of TMPs from other studies on a similar topic (Saising et al 2022). The dominant use of trees could be influenced by the region's tropical climate that upholds the growth of a wide variety of trees (Sikuku et al 2023) and the ethnobotanical familiarity of the life form .…”
Section: Life Forms and Sources Of Medicinal Plantssupporting
confidence: 90%
“…The remaining parts had a PPV of less than one (Figure 3). Leaves are also reported in other ethnobotanical studies in Kenya (Wanga & Nyamboki 2023), South Africa (De Wet et al 2013), Thailand (Saising et al 2022), and Pakistan (Malik et al 2019) as frequently and the preferred plant part used to formulate remedies for managing DDs. The preference utilisation of leaves could be associated with their availability and ease of harvest compared to other plant parts.…”
Section: Plant Parts Used Preparation and Administrationmentioning
confidence: 73%
See 2 more Smart Citations
“…
In Thailand, several polyherbal formulations have been used for treating various diseases, including skin infections. 10 In the present work, a polyherbal formulation for treating skin diseases, known as THR-01, consisting of Rhinacanthus nasutus (Acanthaceae), Quisqualis indica (Combretaceae), Ocimum sanctum (Lamiaceae), Vitex glabrata (Verbenaceae), and Stemona tuberosa (Stemonaceae) was chosen for testing its antioxidant activities and safety. Interestingly, Stemona tuberosa, one of the primary components of this formulation was found to exhibit significant antioxidant properties with low toxicity.
…”
mentioning
confidence: 99%